A rare dentigerous cyst of maxillary central incisor associated with multiple impacted teeth: Case report and review of literature - Pushkar Dahiwal; Sonia Sodhi; Lata Kale; Neha Khambete (Wolters Kluwer Medknow Publications, 2015)
We report a case of a 15-year-old male who presented with a chief complaint of swelling in the maxillary anterior region of the jaw since 5 years. Patient gave a history of trauma to the same region 7 years back. On examination, a large intraoral swelling with multiple missing permanent teeth was noted. On radiographic examination, a large corticated radiolucency surrounding the maxillary left central and lateral incisors and canine was seen in the anterior maxilla. Surgical enucleation was carried out and histopathologic examination confirmed diagnosis of an infected dentigerous cyst. The present case report is unique as the cyst enclosed the three permanent maxillary teeth: Central incisor, lateral incisor, and canine.